Respiratory syncytial virus in severe lower respiratory infections in previously healthy young Ethiopian infants - Abate Yeshidinber Weldetsadik; Frank Riedel (BMC, 2021)
Abstract Background Respiratory Syncytial Virus (RSV) is the commonest cause of acute lower respiratory infections (ALRI) in infants. However, the burden of RSV is unknown in Ethiopia. We aimed to determine the prevalence, seasonality and predictors of RSV infection in young infants with ALRI for the first time in Ethiopia. Methods We performed RSV immuno-chromatographic assay from nasopharyngeal swabs of infants, 29 days to 6 months of age. We included the first 10 eligible infants in each month from June 2018 to May 2019 admitted in a tertiary pediatric center. Clinical, laboratory and imaging data were also collected, and chi-square test and regression were used to assess associated factors with RSV infection. Results Among a total of 117 study children, 65% were male and mean age was 3 months. Bronchiolitis was the commonest diagnosis (49%). RSV was isolated from 26 subjects (22.2%) of all ALRI, 37% of bronchiolitis and 11% of pneumonia patients. Although RSV infection occurred year round, highest rate extended from June to November. No clinical or laboratory parameter predicted RSV infection and only rainy season (Adjusted Odds Ratio (AOR) 10.46 [95%. C.I. 1.95, 56.18]) was independent predictor of RSV infection. Conclusions RSV was isolated in a fifth of young infants with severe ALRI, mostly in the rainy season. Diagnosis of RSV infection in our setting require specific tests as no clinical parameter predicted RSV infection. Since RSV caused less than a quarter of ALRI in our setting, the other causes should be looked for in future studies.